A Study of the Role of the Manufacturing Sector in Zambia’s Economic Growth – A Quantitative Approach - Rhoda Mayawa (International Journal of Engineering and Management Research, 2024)
Zambia has embraced Vision 2030 making it a middle-income nation as a project delivery method. The country faces constraints that have made this provision a challenge. The Manufacturing sector plays a role in contributing to this challenge. The purpose of this study was to understand the contribution of each sector identified as key economic sectors in Vision 2030 towards economic growth, with a bias towards understanding the contribution of the manufacturing sector to economic growth. The study made use of quarterly time-series quantitative secondary data from 2014Q1 to 2021Q4 that was analyzed using the ARDL model through regression analysis. The study found a long-run relationship that exists between the dependent and the independent variables using the ARDL bounds testing approach. The study has found that there is no statistically significant relationship between Economic growth and manufacturing sector output in the long run. However, the study shows that there is a short-run positive effect of manufacturing sector output on Economic Growth in the current period and with a lag of two periods. Therefore, manufacturing sector output is a short-run determinant of economic growth. This, however, is argued to be not ideal as Vision 2030 promotes long-term growth. This is because the manufacturing sector coupled with exports has the potential to accelerate sustainable economic growth in developing countries like Zambia. This Study has established the need for aligning gaps in the manufacturing sector. Therefore, it is proposed that there is a need for sustained relevant investment in the manufacturing sector for it to yield long-term positive effects. Economic growth is very essential for all economies and the role of the manufacturing sector can help achieve this goal.